Peterhof at the Close of an Era: The Imperial Lapidary Factory under the Artistic Direction of Yevgeny Lanceray (1911–1915) - Budrina, Ludmila A. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2025)
This article explores an uncharted aspect of Russian stonecutting art history: the experience of inviting Yevgeny Yevgenyevich Lanceray to serve as artistic director of the imperial lapidary factories. A representative of an extensive family whose influence on the development of Russian art is beyond doubt, this brilliant graphic artist and decorator introduced several innovations to the organization of the artistic process. The objective of this publication is to analyse this process. Drawing from documents in the archive of the imperial Peterhof Lapidary Factory that have not previously been introduced into scholarly circulation, this study explores the practice of delegating design work to leading masters, considering the profile of their main activity as introduced by Lanceray. Thus, leading animal sculptors were engaged to create objects and their details featuring images of animals, while renowned architects and decorators with extensive experience in designing the interiors of mansions and residences were involved in developing a range of interior vases. Furthermore, the uncovered archival material enables us to contemplate the stylistic explorations of the late Art Nouveau era, a resurgence of interest in the national style, and a reversion to neoclassical forms. The meticulous review of the documents allowed for the identification and reattribution of works that had become detached from their original place of creation and their respective authors during their history. This publication fulfils several objectives: it enhances understanding of Lanceray’s creative activity and work as a guest artist at the imperial manufactories, sheds new light on the artistic side of the Peterhof Lapidary Factory during the period before World War I, which has been virtually unexplored previously. The author also makes new attributions for works of stone-cutting art from museum and private collections.